Professional Interpreter Services and the Impact on Hospital Care Outcomes: An Integrative Review of Literature - Kwan, Michelle; Jeemi, Zakia; Norman, Richard; Dantas, Jaya A R (2023)
Migration patterns have rapidly changed in Australia and elsewhere, which have contributed to increasingly culturally and linguistically diverse societies. This requires healthcare sectors to provide professional interpreter services for patients with a language barrier to eliminate healthcare disparities. This integrative review aimed to investigate the impact of professional interpreter services on hospital care outcomes and the associated cost of service provision. A systematic search of five databases was conducted for peer-reviewed articles from January 1996 to December 2020. Data were extracted for the hospital setting, intervention, population, study design, outcomes and key findings. Following the PRISMA guidelines, full-text screening identified 37 articles that were analysed and included. Communication quality, hospital care outcomes and hospital costs were the three main themes identified. Closing the language gap should be a primary consideration to prevent adverse events that affect patient safety and the standard of care in hospitals. The findings of this review indicate the provision of professional interpreter services can enhance hospital care for linguistically diverse patients by improving patient–provider communication. To gain insight into the changing patterns on the outcomes of medical care, further research requires efforts by the hospital administrative system to document complete records of service usage.